The first recurrent intravascular papillary endothelial hyperplasia (Masson’s tumor) of the kidney - Alkan, Erdal (Turk J Urol, 2016)
Intravascular papillary endothelial hyperplasia (IPEH, Masson’s Tumor) of the kidney is an unusual, benign vascular lesion. A rare case of recurrent IPEH in the kidney was presented in this article. A 50-year-old male with a diagnosis of a suspicious mass in the left kidney was referred to our center for robotic partial nephrectomy. Robotic zero ischemia partial nephrectomy was performed due to the suspicion of a renal malignancy. On the basis of the histopathological results, the patient was diagnosed as IPEH. A urinary ultrasound was performed on the 3(rd) postoperative month and a hyper echoic solid lesion, which was in the same localization, was detected. Due to the previous atypical pathological result, computed tomography (CT) guided fine-needle aspiration biopsy from the left renal mass was performed but malignant cytology was not confirmed with this biopsy. On follow-up CT done 6 months later, a persistent suspicious left renal mass, measuring 40 × 30 cm in size was detected with no change in its dimensions and appearance. Additionally, magnetic resonance imaging (MRI) scan revealed a bone lesion of 15 × 10 mm in the left hip, which was not present on previous MRI/CT scans. In view of the solid masses in the left kidney, and left hip on CT and MRI scan suspicious for a probably metastatic renal neoplasm, left radical nephrectomy via a left subcostal transperitoneal incision was performed. The ultimate pathological report of the patient was also supported the diagnosis of Masson’s tumor and any renal malignancy was not encountered The patient was discharged on the 4(th) postoperative day and has been followed up for 4 months without any problems. In this case, we discuss the clinical features, histopathological characteristics, and the management of Masson’s tumor of the kidney in the light of the current literature.